Perineal Massage as a Preventive Effort to Reduce Perineal Rupture in Vaginal Births - Hidayati, Rokhmah; Siswiyanti, Siswiyanti; Puspita Sari, Lutfiana (Poltekkes Kemenkes Surakarta, 2024)
Background: Perineal rupture is a tear that occurs in the midline between the vulva and anus during childbirth. This condition is still commonly experienced by mothers giving birth vaginally, so preventive measures are needed, one of which is perineal massage. This study aims to determine the effect of perineal massage on the incidence of perineal rupture in mothers giving birth in the Prambanan District. Methods: The study design used a quasi-experimental approach with a pretest–posttest control group design. Sampling was conducted using purposive sampling, involving 30 respondents consisting of 15 intervention groups and 15 control groups. The research instrument used a perineal rupture observation sheet, and data analysis was performed using the Mann–Whitney test at a significance level of 0.05. Results: The results showed that the incidence of perineal rupture in the control group was 12 respondents (80%), while in the intervention group it was 6 respondents (40%). The statistical test yielded a p-value of 0.028, which means that perineal massage has a significant effect on reducing the incidence of perineal rupture in pregnant women in the Prambanan District. Conclusion: Perineal massage is effective in reducing the risk of perineal rupture. The recommendation from this study is for midwives to provide education and training on perineal massage to pregnant women as part of their childbirth preparation care.